Magnetic core, magnetic component, and electronic device
By optimizing the particle size distribution and composition of soft magnetic particles in the magnetic core, especially adjusting the spacing of large particles, so that they can be within a specific range, the existing core density and large losses are solved, and better DC superposition characteristics and loss reduction are achieved.
Patent Information
- Application Number
- CN202411518700.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-28
- Filing Date
- 2024-10-29
- Publication Date
- 2025-05-02
AI Technical Summary
The existing powdered magnetic core is difficult to increase the density during molding, resulting in large core loss and poor DC superposition characteristics.
A magnetic core containing soft magnetic particles is adopted, where the particle size distribution and spacing of the large particles are uniform. By adjusting the composition and microstructure of the soft magnetic particles, the average distance between the large particles is within a specific range, and the DC superposition characteristics and losses of the magnetic core are improved.
By optimizing the particle size distribution and composition of soft magnetic particles, the DC superposition characteristics of the magnetic core are significantly improved and the core loss is reduced.
Smart Images

Figure CN119920560A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnetic core, a magnetic component and electronic equipment. Background Art
[0002] Patent Document 1 describes an inductor formed by integrally molding a powder core obtained by compacting metal magnetic powder and a coil portion.
[0003] When metal magnetic powder is used in a powder core, the core loss tends to increase. By using amorphous alloy powder as the metal magnetic powder, the core loss is reduced. However, it is difficult to increase the density of the powder core during molding.
[0004] Patent Documents 2 and 3 describe the use of a mixture of crystalline alloy magnetic powder and amorphous alloy magnetic powder.
[0005] Patent Document 4 describes that by using an amorphous soft magnetic powder having a high average practical sphericity, it is possible to provide an inductor or the like having lower loss than conventional ones.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-309024
[0009] Patent Document 2: Japanese Patent Application Publication No. 2004-197218
[0010] Patent Document 3: Japanese Patent Application Publication No. 2004-363466
[0011] Patent Document 4: Japanese Patent No. 5110660 Summary of the invention
[0012] Technical problem to be solved by the invention
[0013] The object of the present invention is to obtain a magnetic core having improved direct current superposition characteristics and improved core loss.
[0014] Means for solving technical problems
[0015] In order to achieve the above object, an exemplary embodiment of a magnetic core according to one aspect of the present invention is a magnetic core comprising soft magnetic particles, wherein:
[0016] In the volume-based particle size distribution of the soft magnetic particles, the soft magnetic particles having a particle diameter of (0.5×D50) or more are defined as large particles,
[0017] When the average value of the distance from a certain large particle to the three large particles closest to the large particle is set as AL, and the median value of AL calculated for all large particles is set as M,
[0018] 1.0μm<M<(0.5×D50) is satisfied.
[0019] D50 may be 4.0 μm or more and 60.0 μm or less.
[0020] In order to achieve the above object, another aspect of the present invention relates to a magnetic core of an exemplary embodiment, which is a magnetic core comprising soft magnetic particles, wherein:
[0021] In the volume-based particle size distribution of the soft magnetic particles, the soft magnetic particles having a particle diameter of (0.5×D50) or more are defined as large particles,
[0022] When the average value of the distance from a certain large particle to the three large particles closest to the large particle is set as AL, and the median value of AL calculated for all large particles is set as M,
[0023] Satisfies 0.35μm<M<(0.5×D50), and
[0024] D50 is 0.80 μm or more and less than 4.0 μm.
[0025] The following description also applies to the magnetic core according to any of the above-described exemplary embodiments.
[0026] Alternatively, at least a portion of the soft magnetic particles may be composed of a composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f (atomic ratio) means,
[0027] X1 is one or more selected from Co and Ni,
[0028] X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements,
[0029] X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W,
[0030] Satisfies 0≤p≤0.5,
[0031] 2.00≤a≤20.00,
[0032] 0.00≤b≤14.00,
[0033] 0.00≤c≤15.00,
[0034] 0.00≤d≤5.00,
[0035] 0.00≤e≤3.00,
[0036] 0.00≤f≤9.00, and
[0037] 70.00≤100-(a+b+c+d+e+f)≤96.00.
[0038] At least a part of the soft magnetic particles may contain only Fe, or contain Fe and Co and / or Ni.
[0039] A magnetic component according to an exemplary embodiment of the present invention includes any one of the above-described magnetic cores.
[0040] An electronic device according to an exemplary embodiment of the present invention includes any one of the above-described magnetic cores. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a SEM image of a cross section of a magnetic core according to an exemplary embodiment of the present invention.
[0042] Figure 2 It is a graph showing the distribution of various lengths.
[0043] Figure 3 This is an example of a graph obtained by X-ray crystal structure analysis.
[0044] Figure 4 is through Figure 3 An example of a pattern obtained by performing profile fitting on a graph of . DETAILED DESCRIPTION
[0045] Next, embodiments of the present invention will be described.
[0046] (First Embodiment)
[0047] The magnetic core of the present embodiment includes soft magnetic particles. The soft magnetic particles include at least large particles described below.
[0048] The method for observing the soft magnetic particles contained in the magnetic core is not particularly limited. For example, a method of observing the cross section of the magnetic core using SEM, TEM, etc. can be cited. In addition, the cross section obtained by cutting the magnetic core can also be ground.
[0049] The size of the observation range in the cross section of the magnetic core is not particularly limited. The observation range is set in a manner such that the soft magnetic particles contained in the observation range add up to more than 10,000. It is preferred to set one observation range or multiple continuous observation ranges. However, multiple observation ranges can also be set at mutually separated locations.
[0050] There is no particular limitation on the magnification and resolution when observing the cross section of the magnetic core. The magnification may be 500 to 3000 times, and the resolution may be 2560×1920 or more.
[0051] The particle size of all soft magnetic particles included in each observation range is measured. The particle size of each soft magnetic particle is the Heywood diameter. The Heywood diameter refers to the projected area circle equivalent diameter. The Heywood diameter of the soft magnetic particles in this embodiment is (4S / π) when the area of the soft magnetic particles in the cross section is set to S. 1 / 2 .
[0052] The volume of each soft magnetic particle is calculated by assuming that the shape of each soft magnetic particle is spherical. That is, the volume of each soft magnetic particle is calculated by assuming that the particle size of each soft magnetic particle is d (πd 3 The volume of all the soft magnetic particles is calculated by the above method.
[0053] By the above method, the particle diameter and volume of all the soft magnetic particles included in each observation range are calculated.
[0054] Next, based on the particle size and volume of each soft magnetic particle calculated by the above method, the particle size distribution of the soft magnetic particles on a volume basis is calculated.
[0055] The calculation of the particle size distribution requires setting intervals. In this embodiment, 100 intervals are set according to the following formula. Let i = 1, 2, 3 ... 100, x i is equal to i, y i is the average particle size in interval i (unit: μm). In addition, exp(X)=e X , e is the base of natural logarithms.
[0056] y i =0.02×exp(x i ×0.085)
[0057] For example, the average particle size of the first interval from the smallest is 0.02×e 0.085 =0.022μm. Similarly, the average particle size of the second interval is 0.02×e 0.17 =0.024 μm, and the average particle size of the 50th interval is 0.02×e 4.25=1.402μm, the average particle size of the 100th interval is 0.02×e 8.5 =98.295μm.
[0058] Then, the volume-based particle size distribution of the soft magnetic particles is calculated using the intervals set by the above method. An example of the results is shown in Figure 2 . Figure 2 The curve shown is a graph showing the particle size distribution of soft magnetic particles on a volume basis. Figure 2 In the graph shown, the horizontal axis represents the particle size.
[0059] exist Figure 2 The position of D50 / 2 in the volume-based particle size distribution of the soft magnetic particles is shown in . In addition, D50 in the volume-based particle size distribution of the soft magnetic particles refers to the particle size when the cumulative relative frequency on a volume basis is 50% (0.50).
[0060] Then, the soft magnetic particles having a particle size of (0.5×D50) or more are defined as large particles. The soft magnetic particles of this embodiment include large particles. The soft magnetic particles of this embodiment may also include particles that are not classified as large particles, that is, particles having a particle size of less than (0.5×D50).
[0061] Compared with the case where the distribution of the distance between large particles is outside the specific range, the magnetic core of the present embodiment can improve the DC superposition characteristics by making the distribution of the distance between large particles within the specific range.
[0062] The average value of the distance from a certain large particle to the three large particles closest to the large particle is set as AL. Specifically, among the large particles, the large particles within the third particle from the particle with the shortest distance from the surface of the large particle are identified. Then, the distances from the surface of the large particle to the surface of the large particles within the third particle are measured and averaged to obtain AL.
[0063] AL is measured for all large particles within the observation range, and the median value of AL is set to M.
[0064] exist Figure 2 The position of M is shown in FIG. Moreover, the soft magnetic particles contained in the magnetic core of the present embodiment satisfy 1.0 μm<M<(0.5×D50). In addition, Figure 1 This is an example of a SEM image of a cross section of a magnetic core satisfying 1.0 μm<M<(0.5×D50).
[0065] When M is too small, the distance between large particles is too short. As a result, the magnetization of the large particles is likely to become non-uniform, and the DC superposition characteristics are likely to deteriorate.
[0066] When M is too large, the distance between large particles is too long, the magnetic resistance between large particles is likely to increase, and the magnetic permeability is likely to decrease.
[0067] By setting M within the above range, the distance between large particles is within a preferred range. As a result, it is easy to improve the DC superposition characteristics while maintaining the magnetic permeability.
[0068] The DC superposition characteristics of the magnetic core are improved when the soft magnetic particles contained in the magnetic core satisfy 1.0 μm<M<(0.5×D50), compared with the case where the conditions are substantially the same except that M is too small and the case where the conditions are substantially the same except that M is too large.
[0069] The value of D50 is not particularly limited, and may be, for example, 4.0 μm to 60.0 μm, or 8.0 μm to 45.0 μm.
[0070] The value of M is not particularly limited, and may be, for example, 1.10 μm or more and 15.00 μm or less.
[0071] There is no particular restriction on the total area ratio of the soft magnetic particles to the entire cross section of the magnetic core. For example, it can be 70% to 95%. If the total area ratio is too small, the filling rate of the soft magnetic particles in the magnetic core is too low, so the magnetic permeability is likely to decrease.
[0072] The total area ratio of the large particles to the entire cross section may be 70% or more.
[0073] The average circularity of the large particles in the entire cross section may be 0.50 or more and 0.99 or less.
[0074] In addition, the large particles and / or particles other than the large particles of the present embodiment may also have a coating on the surface. The coating may also be an insulating coating. The type of the coating is not particularly limited, as long as it is formed by a coating commonly used in the technical field. Examples include iron oxides, phosphates, silicates (water glass), soda lime glass, borosilicate glass, lead glass, aluminosilicate glass, borate glass, sulfate glass, and the like. Examples of phosphates include magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate. Examples of silicates include sodium silicate. In addition, the thickness of the coating is not particularly limited either. For example, it may be on average more than 5 nm and less than 100 nm.
[0075] In addition, the magnetic core of the present embodiment may also contain resin in addition to the soft magnetic particles. The type of resin is not particularly limited. For example, silicone resin or epoxy resin is exemplified. The content of resin in the magnetic core is also not particularly limited. For example, relative to 100 parts by mass of soft magnetic particles, it can be more than 1.0 parts by mass and less than 5.0 parts by mass, or it can be more than 1.5 parts by mass and less than 3.5 parts by mass. In the case of too much resin, the filling rate of soft magnetic particles is easily reduced, and the magnetic permeability is easily reduced. If the filling rate of soft magnetic particles is increased in order to increase the magnetic permeability, the DC superposition characteristics are easily reduced.
[0076] Furthermore, the portion other than the magnetic body (eg, soft magnetic particles) in the cross section of the magnetic core may be occupied by the resin, or by the resin and the voids.
[0077] There is no particular restriction on the fine structure of the soft magnetic particles. For example, the soft magnetic particles may have a structure including amorphous matter or a structure composed of crystals. The soft magnetic particles (especially large particles) may also have a nano-heterogeneous structure. The nano-heterogeneous structure refers to a structure containing initial microcrystals with an average crystal particle size of 0.3 nm or more and 10 nm or less in amorphous matter. In the case where the soft magnetic particles have a structure composed only of amorphous matter or a nano-heterogeneous structure, the amorphous rate X described later is 85% or more. In the case where the soft magnetic particles have a structure composed of crystals, the amorphous rate X described later is less than 85%. When the filling rate is roughly the same, when the soft magnetic particles (especially large particles) have a nano-heterogeneous structure, the relative magnetic permeability is improved compared to the case where the soft magnetic particles (especially large particles) have a structure composed only of amorphous matter. Furthermore, the soft magnetic particles (especially large particles) may also have a structure composed of crystals and an average crystal particle size of 1 nm or more and 30 nm or less and a crystal particle size of up to 100 nm or less (nano-crystalline structure). Under the situation that filling rate is roughly the same, when soft magnetic particles (particularly macroparticles) have nanocrystalline structure, the relative magnetic permeability of magnetic core further improves.In addition, in the soft magnetic particles that comprise crystallization, particularly nanocrystal, usually a particle comprises a plurality of crystals.That is, the particle diameter of soft magnetic particles is different from the crystal grain diameter.The calculation method of crystal grain diameter is not particularly limited.For example, can enumerate by analyzing the half width obtained by XRD measurement and evaluating the method for calculating crystal grain diameter and by using TEM to observe crystallization and calculate the method for crystal grain diameter.
[0078] Further, the nanocrystal included in the soft magnetic particles (particularly macroparticles) can also be a Fe-based nanocrystal.Fe-based nanocrystals refer to that average crystal grain size is nano-level (specifically 0.1nm above and 100nm below) and the crystalline structure of Fe is the crystallization of bcc (body-centered cubic lattice structure).The calculation method of the average crystal grain size of Fe-based nanocrystals is not particularly limited.For example, the method of calculating the crystal grain size by analyzing the half width obtained by XRD measurement and evaluating the crystallite size and the method of calculating the crystal grain size by using TEM to observe.In addition, confirming that the method of bcc crystalline structure is not particularly limited either.For example, the method of using XRD to confirm and the method of confirming by analyzing the electron diffraction pattern obtained by using TEM can be enumerated.
[0079] In the present embodiment, the average crystal grain size of the Fe-based nanocrystals can also be 1 to 30 nm. The saturation flux density of the soft magnetic particles having a structure composed of such Fe-based nanocrystals tends to be high, and the coercive force tends to be low. That is, the soft magnetic properties are easily improved. That is, by including the soft magnetic particles, it is easy to make the magnetic core (magnetic molded body) have low coercive force and high relative permeability. Moreover, because the saturation flux density of the magnetic core containing the soft magnetic particles increases, the DC superposition characteristics of the magnetic core are improved. Thus, by using soft magnetic particles having a structure composed of Fe-based nanocrystals, it is easy to improve the properties of the magnetic core.
[0080] The method for confirming the fine structure of the soft magnetic particles is not particularly limited, and can be confirmed by, for example, XRD.
[0081] In this embodiment, soft magnetic particles having an amorphization rate X of 85% or more represented by the following formula (1) are regarded as having a structure consisting only of amorphous matter or a nano-heterostructure, and soft magnetic particles having an amorphization rate X of less than 85% are regarded as having a structure consisting of crystals.
[0082] X=100-(Ic / (Ic+Ia)×100)……(1)
[0083] Ic: Crystalline scattering integrated intensity
[0084] Ia: Amorphous scattering integrated intensity
[0085] The amorphous ratio X is obtained by performing X-ray crystal structure analysis on the soft magnetic particles using XRD to identify the phase, reading the peak of Fe or the compound after crystallization (Ic: integrated intensity of crystalline scattering, Ia: integrated intensity of amorphous scattering), and calculating the crystallization ratio based on the peak intensity, which is calculated according to the above formula (1). The calculation method is described in more detail below.
[0086] The soft magnetic particles of this embodiment were analyzed by X-ray crystal structure using XRD, and the Figure 3 The peak shape is fitted using the Lorentz function of the following formula (2), and we get Figure 4 The crystal component pattern α showing the integrated intensity of crystalline scattering is shown in FIG. c , amorphous component pattern α representing the integrated intensity of amorphous scattering a and the pattern α that combines them c+a The amorphization rate X is calculated by the above formula (1) based on the crystalline scattering integrated intensity and the amorphous scattering integrated intensity of the obtained pattern. In addition, the measurement range is set to the range of diffraction angle 2θ=30° to 60° in which the halo originating from the amorphous can be confirmed. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated using the Lorentz function is within 1%.
[0087]
[0088] h: peak height
[0089] u: peak position
[0090] w: half width
[0091] b: background height
[0092] The composition of the soft magnetic particles is not particularly limited. In addition, the composition of the soft magnetic particles described below may be the average composition of all the soft magnetic particles contained in the magnetic core.
[0093] At least a portion of the soft magnetic particles may also be composed of the composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f (atomic ratio) means,
[0094] Alternatively, X1 may be one or more selected from Co and Ni,
[0095] X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements,
[0096] X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W,
[0097] It can also satisfy 0≤p≤0.5,
[0098] 2.00≤a≤20.00,
[0099] 0.00≤b≤14.00,
[0100] 0.00≤c≤15.00,
[0101] 0.00≤d≤5.00,
[0102] 0.00≤e≤3.00,
[0103] 0.00≤f≤9.00, and
[0104] 70.00≤100-(a+b+c+d+e+f)≤96.00.
[0105] A magnetic core including soft magnetic particles having a composition within the above range is likely to have excellent DC superposition characteristics.
[0106] The composition of at least a part of the soft magnetic particles may be the average composition of the large particles.
[0107] The method for analyzing the composition of the soft magnetic particles is not particularly limited. For example, it can be confirmed by ICP analysis. In addition, for the cross section of the molded body containing soft magnetic particles, SEM-EDS or EPMA etc. can also be used for analysis.
[0108] Next, each component of the soft magnetic particles will be described in detail.
[0109] X1 is one or more selected from Co and Ni. It may also contain soft magnetic particles with 0≤p≤0.5. A magnetic core containing soft magnetic particles whose Fe content is greater than the total content of Co and Ni is likely to have excellent DC superposition characteristics.
[0110] The soft magnetic particles may contain a content (a) of B satisfying 2.00≤a≤20.00. The magnetic core containing the soft magnetic particles having a content of B within the above range is likely to have excellent DC superposition characteristics.
[0111] The soft magnetic particles may be included in which the P content (b) satisfies 0.00≤b≤14.00. The magnetic core including the soft magnetic particles having the P content within the above range is likely to have excellent DC superposition characteristics.
[0112] The soft magnetic particles may contain Si content (c) satisfying 0.00≤c≤15.00. The magnetic core containing the soft magnetic particles having Si content within the above range is likely to have excellent DC superposition characteristics.
[0113] The soft magnetic particles may be included in which the content (d) of C satisfies 0.00≤d≤5.00. The magnetic core including the soft magnetic particles having a C content within the above range is likely to have excellent DC superposition characteristics.
[0114] The soft magnetic particles may be included in which the content (e) of X2 satisfies 0.00≤e≤3.00. The magnetic core including the soft magnetic particles in which the content of X2 is within the above range is likely to have excellent DC superposition characteristics.
[0115] The soft magnetic particles may be included in which the content (f) of X3 satisfies 0.00≤f≤9.00. The magnetic core including the soft magnetic particles in which the content of X3 is within the above range is likely to have excellent DC superposition characteristics.
[0116] It may also contain soft magnetic particles satisfying 70.00≤100-(a+b+c+d+e+f)≤96.00. The total content of Fe and X1 in the soft magnetic particles is 70.00at% or more and 96.00at% or less. The magnetic core containing soft magnetic particles having a total content of Fe and X1 within the above range is likely to become a magnetic core having excellent DC superposition characteristics.
[0117] The soft magnetic particles may also contain oxygen. Moreover, the oxygen content relative to 100% by mass of the soft magnetic particles may be between 0 ppm and 10,000 ppm on a mass basis. A magnetic core containing soft magnetic particles having an oxygen content within the above range is likely to have excellent DC superposition characteristics.
[0118] In addition, the soft magnetic particles may contain elements other than Fe, X1, B, P, Si, C, X2 and X3 as inevitable impurities within a range that does not have a significant effect on the performance. The oxygen content is as described above. In addition, the soft magnetic particles may contain elements other than oxygen in an inevitable impurity content of less than 0.1% by mass relative to 100% by mass of the soft magnetic particles.
[0119] At least a part of the soft magnetic particles may contain only Fe, or contain Fe and Co and / or Ni as main components.
[0120] Containing only Fe, or containing Fe and Co and / or Ni as main components means that the content of Fe in the soft magnetic particles is 15 at % to 100 at %, and the total content of Fe, Co and Ni is 50 at % to 100 at %.
[0121] In addition, when only Fe or Fe and Co and / or Ni are contained as the main components, the types of elements other than the main components are not particularly limited, and examples thereof include Cr, Al, Si, B, P, C, O, Nb, Zr, Ta, Mn, V, Cu, S, and the like.
[0122] In the case where soft magnetic particles (especially large particles) have a structure composed of nanocrystals, as the composition of the soft magnetic particles, Fe-Si-B-Nb-Cu system, Fe-BP-Si-Cu system, Fe-BP-Si-Nb-Cr system, etc., which are easy to have a structure composed of nanocrystals, are exemplified.
[0123] In the manufacturing method of the magnetic core described later, when the soft magnetic powder containing the soft magnetic particles having the above composition is heat-treated, Fe-based nanocrystals are easily precipitated in the soft magnetic particles. In other words, the soft magnetic powder having the above composition is easy to be used as the starting material of the soft magnetic powder having the soft magnetic particles that precipitate Fe-based nanocrystals.
[0124] Under the situation that Fe-based nanocrystal is separated out in soft magnetic particles by thermal treatment, the soft magnetic particles before the thermal treatment can have the structure that is only made of amorphous, and can also have the nano heterostructure that initial microcrystal is present in the amorphous. In addition, the average grain size of initial microcrystal can also be below 10nm above 0.3nm. In addition, under the situation that soft magnetic particles have the structure that is only made of amorphous or nano heterostructure, the amorphization rate X described later is more than 85%.
[0125] In the case where soft magnetic particles (especially large particles) have a structure composed of amorphous substances, as the composition of the soft magnetic particles, examples include Fe-Co-BP-Si-Cr system, Fe-Co-BP-Si system, Fe-B-Si-C-Cr system, Fe-B-Si-C system, etc., which are easy to have a structure composed of amorphous substances.
[0126] In the case where soft magnetic particles (especially large particles) have a structure composed of crystals, as the composition of the soft magnetic particles, Fe-based, Fe-Co-based, Fe-Co-Si-based, Fe-Si-Cr-based, Fe-Co-Si-Cr-based, Fe-Si-Al-based, etc., which are easy to have a structure composed of crystals, are exemplified.
[0127] The composition of the soft magnetic particles (particularly particles other than large particles) is not particularly limited. The composition of the soft magnetic particles is not particularly limited. At least a portion of the soft magnetic particles may contain only Fe, or contain Fe and Co, Ni and / or Si as main components.
[0128] Containing only Fe, or containing Fe and Co, Ni and / or Si as main components means that the Fe content in the soft magnetic particles is from 15 at % to 100 at %, and the total content of Fe, Co, Ni and Si is from 50 at % to 100 at %.
[0129] In addition, when only Fe or Fe and Co, Ni and / or Si are contained as main components, the types of elements other than the main components are not particularly limited, and examples thereof include Cr, Al, B, P, C, O, Nb, Zr, Ta, Mn, V, Cu, S, and the like.
[0130] By making the soft magnetic particles (particularly particles other than large particles) have the above composition, it is easy to produce a magnetic core having high magnetic characteristics.
[0131] The method for manufacturing the magnetic core according to the present embodiment will be described below, but the method for manufacturing the magnetic core is not limited to the method described below.
[0132] First, a soft magnetic powder including the soft magnetic particles of the present embodiment is prepared. The soft magnetic powder of the present embodiment can be obtained by mixing a soft magnetic powder that will eventually become mostly large particles and a soft magnetic powder that will eventually become mostly particles other than large particles.
[0133] The soft magnetic powder that is ultimately mostly large particles can be produced by, for example, water atomization or gas atomization. The gas atomization method is described below. The water atomization method is the same as the gas atomization method except that the high-pressure gas sprayed toward the molten metal is replaced with water.
[0134] In the gas atomization method, the molten metal obtained by melting the raw material metal is powdered by the gas atomization method to produce soft magnetic powder. The composition of the molten metal is the same as the composition of the soft magnetic particles finally obtained. At this time, the molten metal drips from a container formed with a discharge port toward the cooling part. The temperature of the molten metal is the injection temperature. The injection temperature is not particularly limited. For example, it is 1200°C or more and 1600°C or less. The higher the injection temperature, the easier it is for the average circularity to approach 1, and the easier it is for the average particle size to become smaller.
[0135] In addition, a gas injection nozzle having a gas injection port is arranged in a manner surrounding the above-mentioned discharge port. High-pressure gas (the injection pressure (gas pressure) is a gas of not less than 2.0 MPa and not more than 10 MPa) is injected from the gas injection port toward the molten metal dripping from the discharge port. As a result, the molten metal becomes a plurality of droplets. By controlling the pressure of the high-pressure gas at this time, the particle size of the soft magnetic powder and the shape of the soft magnetic powder can be changed. Specifically, when the injection amount of the molten metal is the same, the higher the pressure of the high-pressure gas, the smaller the particle size of the soft magnetic powder can be obtained. That is, the particle size of the soft magnetic powder or the shape of the soft magnetic powder can be changed according to the ratio of the pressure of the high-pressure gas to the injection amount of the molten metal.
[0136] As the gas injected from the gas injection port, an inert gas such as nitrogen, argon, helium, or a reducing gas such as ammonia decomposition gas is preferred. Alternatively, air may be used when the molten metal is not easily oxidized.
[0137] The shape of the cooling part where the molten metal is dripped is not particularly limited. For example, a cylinder having a cooling liquid flow that collides with the molten metal can also be made. In this case, by controlling the injection amount of the molten metal, the high-pressure gas pressure shown above, and the water pressure of the cooling liquid flow, the particle size or average circularity of the large particles in the magnetic core finally obtained can be changed. That is, the particle size or average circularity of the soft magnetic particles is controlled under the balance of the injection amount of the molten metal, the high-pressure gas pressure, and the water pressure of the cooling liquid flow. The injection amount of the molten metal can also be more than 0.5kg / min and less than 4.0kg / min, and the water pressure can also be more than 5.0MPa and less than 20.0MPa. Specifically, the larger the injection amount, the easier it is for the particle size to become larger. In addition, the lower the water pressure, the easier it is for the average circularity of the large particles to approach 1.
[0138] The molten metal discharged into the coolant flow collides with the coolant flow, further breaks, refines, changes shape, and is cooled and solidified to become a solid soft magnetic powder. The soft magnetic powder discharged together with the coolant is separated into the coolant in an external storage tank or the like and taken out. In addition, the type of coolant is not particularly limited. For example, cooling water can be used.
[0139] The obtained soft magnetic powder may also be subjected to heat treatment. The conditions of the heat treatment are not particularly limited. For example, the heat treatment may be performed at 400 to 700° C. for 0.1 to 10 hours. By performing the heat treatment, when the fine structure of the soft magnetic particles is a nano-heterogeneous structure having only an amorphous structure or an initial microcrystal existing in an amorphous structure, the fine structure of the soft magnetic particles tends to become a structure composed of nanocrystals.
[0140] The method for producing the soft magnetic powder that ultimately becomes mostly particles other than large particles is not particularly limited, and it can be produced by various powdering methods such as a liquid phase method, a spray pyrolysis method, and a melting method.
[0141] The average particle size of the soft magnetic powder, most of which will eventually become particles other than large particles, can be controlled by appropriately removing coarse powder and / or fine powder using an air classifier.
[0142] In addition, the above-mentioned soft magnetic powders may also be coated at this time. The method for forming the coating is not particularly limited.
[0143] Next, a magnetic core is made from the above-mentioned soft magnetic powders. First, the above-mentioned soft magnetic powders are weighed. Hereinafter, the soft magnetic powder that eventually becomes mostly large particles is referred to as powder A, and the soft magnetic powder that eventually becomes mostly particles other than large particles is referred to as powder B. The mixing ratio of the soft magnetic powders is not particularly limited. For example, the proportion of powder A may be 30% by mass or more and 90% by mass or less. The proportion of powder B may also be 10% by mass or more and 70% by mass or less.
[0144] In addition to powder A and powder B, powder C having an average particle size between powder A and powder B may also be used. Like powder B, powder C is also likely to become particles that are mostly not equivalent to large particles in the end. The composition and fine structure of powder C are not particularly limited. It may be the same as powder A, the same as powder B, or different from both powder A and powder B. In the case of using powder C having an average particle size between powder A and powder B in addition to powder A and powder B, the total ratio of powder B and powder C may also be 10% by mass or more and 70% by mass or less.
[0145] Next, the weighed powder B is agglomerated. Specifically, after the powder B is mixed with the resin, the powder B mixed with the resin is filled into a mold and compressed. Powder B is set to 100 parts by mass, and the amount of resin added may be between 0.1 parts by mass and 0.3 parts by mass. The less the amount of resin added, the more difficult it is for powder B to agglomerate. In addition, the higher the pressure value during compression, the more the powder B will agglomerate, and the easier it is for the M of the magnetic core to become larger. The pressure value during compression may be, for example, between 10 MPa and 1000 MPa, or between 40 MPa and 600 MPa.
[0146] Next, powder A, condensed powder B and resin are kneaded to prepare a resin mixture. When powder C is used, powder C is also kneaded. The content of the soft magnetic powder in the resin mixture is set to 100 parts by mass, and the content of the resin can be more than 1.0 parts by mass and less than 5.0 parts by mass, or more than 1.5 parts by mass and less than 3.5 parts by mass. The less the amount of resin, the more difficult it is to compress and mold the soft magnetic powder. In addition, the strength of the magnetic core obtained by compression molding the soft magnetic powder is more likely to decrease, and it is easy to become difficult to handle.
[0147] The agglomerated powder B is crushed to some extent by kneading. The higher the pressure value during compression, the harder it is to crush the powder B, and the lower the pressure value during compression, the easier it is to crush the powder B.
[0148] Then, the obtained resin mixture is filled into a mold for compression molding to obtain a magnetic core. The molding pressure during compression molding is not particularly limited. For example, it can be 98 MPa or more and 981 MPa or less. In addition, the resin contained in the obtained magnetic core can also be thermally cured.
[0149] The composition and fine structure of the soft magnetic particles contained in the soft magnetic powder before compression molding and the composition and fine structure of the soft magnetic particles contained in the magnetic core after compression molding are usually the same.
[0150] As mentioned above, the magnetic core (magnetic molded body) of this embodiment has been described, but the magnetic core (magnetic molded body) of the present invention is not limited to the above-mentioned embodiment.
[0151] In addition, the use of the magnetic core of the present invention is not particularly limited. For example, coil components (magnetic components) such as inductors, chokes, and transformers can be cited. Electronic devices such as DC-DC converters using the magnetic core of the present invention can also be cited.
[0152] (Second Embodiment)
[0153] Next, a second embodiment will be described. Matters not particularly described are the same as those of the first embodiment.
[0154] The soft magnetic particles contained in the magnetic core of the present embodiment satisfy 0.35 μm<M<(0.5×D50), and D50 is 0.80 μm or more and less than 4.0 μm.
[0155] In the case where the D50 of the soft magnetic particles contained in the magnetic core is 0.80 μm or more and less than 4.0 μm, when 0.35 μm<M<(0.5×D50) is satisfied, the DC superposition characteristics of the magnetic core are improved compared to the case where the conditions are substantially the same except that M is too small and the case where the conditions are substantially the same except that M is too large, and the core loss is improved. In the case where D50 is too small, even if M is greater than 0.35 μm, the core loss of the magnetic core is difficult to improve.
[0156] [Example]
[0157] Hereinafter, the present invention will be described based on more detailed examples, but the present invention is not limited to these examples.
[0158] (Experimental Example 1)
[0159] In Experimental Example 1, a powder A, which is mostly large particles, was produced by gas atomization. The composition of the powder A was set to be a Fe-Co-BP-Si-Cr system composition. Specifically, the composition was set to be 57.4Fe-24.6Co-11.0B-3.0P-3.0Si-1.0Cr in terms of atomic ratio.
[0160] Regarding the conditions of the gas atomization method, the pressure of the high-pressure gas is set to 2.0 MPa or more and 10 MPa or less; the ejection rate of the molten metal is set to 0.5 kg / min or more and 4.0 kg / min or less. The atomization conditions and classification conditions are appropriately controlled so that the median particle size (D50) of the obtained powder A on a volume basis becomes 20 μm. In addition, in the classification of the powder A, at least sieve classification using a sieve with a mesh size of 63 μm is performed.
[0161] By ICP analysis, it was confirmed that the composition of the master alloy of each sample was substantially the same as the composition of powder A. It was confirmed that the volume-based median particle size (D50) of the obtained powder A was 20 μm. The volume-based median particle size of powder A was measured by laser diffraction using a dry particle size distribution measuring device.
[0162] Carbonyl iron powder is used as powder B, which ultimately becomes mostly particles other than large particles. That is, the composition of the soft magnetic particles contained in powder B is set to a composition containing substantially only Fe. In addition, by using an air flow classifier to appropriately remove coarse powder and / or fine powder, the median particle size (D50) of powder B on a volume basis is made to be 0.8 μm. By ICP analysis, it is confirmed that the composition of powder B is the target composition. Using a dry particle size distribution measuring device, it is confirmed by laser diffraction that the median particle size (D50) of the obtained powder B on a volume basis is 0.8 μm.
[0163] Each powder was subjected to X-ray diffraction measurement (XRD) to measure the amorphization rate X. When the amorphization rate X is 85% or more, it is assumed to have a structure consisting of amorphous. When the amorphization rate X is less than 85% and the average crystal grain size is less than 100nm, it is assumed to have a structure consisting of nanocrystals. When the amorphization rate X is less than 85% and the average crystal grain size is greater than 100nm, it is assumed to have a structure consisting of crystals. In Experimental Example 1, it was confirmed that all powders A had a structure consisting of amorphous, and all powders B had a structure consisting of crystals.
[0164] Next, powder B is agglomerated. First, powder B and epoxy resin are mixed. The amount of epoxy resin added to powder B is set to 0.2 parts by mass relative to 100 parts by mass of powder B. Next, 1 g of powder B mixed with epoxy resin is filled into a cylindrical mold with a diameter of 8 mm Φ. Next, it is agglomerated by compressing at the pressure value shown in Table 1. In the case of producing more than 1 g of agglomerated powder B, the above steps are repeated multiple times. In addition, in sample number 1, powder B is not compressed and is not agglomerated.
[0165] Next, powder A, condensed powder B, and epoxy resin were kneaded to obtain a resin mixture. In addition, in sample number 1, powder A, powder B, and epoxy resin were kneaded to obtain a resin mixture. The mixing ratio of powder A and powder B was set to 80:20 on a mass basis. When the total of powder A and powder B was set to 100 parts by mass, the content of epoxy resin was set to 2.0 parts by mass to 3.0 parts by mass. The content of epoxy resin was controlled so that the relative permeability μ of the final magnetic core was 30.
[0166] Next, the resin mixture is filled into a ring-shaped mold and press-molded to obtain a ring-shaped molded body. The molding pressure is appropriately controlled within a range of 98 MPa to 981 MPa so that the relative magnetic permeability μ of the finally obtained magnetic core becomes 30.
[0167] Then, the epoxy resin contained in the obtained molded body was thermally cured to obtain a magnetic core. The heat treatment conditions were set at 180° C. for 60 minutes. The dimensions of the magnetic core were set to an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a thickness of 2.5 mm.
[0168] The cross section of the magnetic core of each sample cut parallel to the molding direction (height direction) was observed using SEM (SU-5000 manufactured by HITACHI HIGH-TECH CORPORATION), and D50 was calculated by the above method.
[0169] Furthermore, M was calculated by the above method and compared with 1.0 μm and D50 / 2. The results are shown in Table 1.
[0170] The relative magnetic permeability μ of the toroidal core of each sample was measured by the following method. First, a polyurethane copper wire (UEW wire) was wound around the toroidal core. Then, an LCR meter (4284A manufactured by Agilent Technologies) was used to measure the inductance of the toroidal core at a frequency of 1 MHz without applying a direct current, and the relative magnetic permeability μ was calculated based on the obtained inductance. The results are shown in Table 1.
[0171] Furthermore, in order to evaluate the DC superposition characteristics of the toroidal core of each sample, Isat was measured. For the toroidal core of each sample, the greater the DC current applied, the lower the relative permeability. When the relative permeability of the toroidal core is measured while applying a DC current, the value of the DC current when the relative permeability decreases by 10% from μ is set as Isat. The results are shown in Table 1.
[0172] Furthermore, the Isat of a sample under the same conditions except that the powder B was not agglomerated was used as a reference, and the improvement rate of Isat relative to the Isat of the sample was shown in Table 1. The case where the improvement rate of Isat was 5.0% or more was considered to have good DC superposition characteristics, the case where it was 7.5% or more was considered to have better DC superposition characteristics, and the case where it was 15.0% or more was considered to have particularly good DC superposition characteristics. The results are shown in Table 1.
[0173] Furthermore, the core loss (core loss) of the toroidal core of each sample was evaluated. Specifically, for each toroidal core, the primary winding was wound 24 times and the secondary winding was wound 12 times. Then, the iron loss was measured at 3 MHz, 10 mT, and 20 to 25°C using a BH analyzer (SY-8232 manufactured by Iwasaki Communication Equipment Co., Ltd.).
[0174] Furthermore, the improvement rate of the core loss relative to the core loss of the sample under the same conditions except that the powder B was not agglomerated was calculated as a reference. The results are shown in Table 1. When D50 is 4.0 μm or more, the improvement rate of the core loss is considered to be good when the improvement rate of the core loss is 0.1% or more.
[0175]
Table 1
[0176]
[0177] According to Table 1, in each embodiment (sample numbers 3 to 10) in which 1.0 μm<M<(0.5×D50) is satisfied by agglomerating powder B, the DC superposition characteristics are improved and the core loss is improved, compared with the comparative example (sample number 1) in which M is too small because powder B is not agglomerated. However, in the comparative example (sample number 11) in which M is too large because powder B is excessively agglomerated, the DC superposition characteristics are not sufficiently improved compared with sample number 1.
[0178] (Experimental Example 2)
[0179] Sample Nos. 1 and 6 were tested under substantially the same conditions except that the mixing ratio of powder A and powder B was changed. The results are shown in Table 2. In Tables 2 to 16, Isat and core loss are omitted.
[0180]
Table 2
[0181]
[0182] According to Table 2, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in each embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even if the mixing ratio of powder A and powder B is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0183] (Experimental Example 3)
[0184] Sample Nos. 1 and 6 were run under substantially the same conditions except that the volume-based median diameter (D50) of the powder A was changed. The results are shown in Table 3.
[0185]
Table 3
[0186]
[0187] According to Table 3, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in each embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even if the volume-based median particle size (D50) of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0188] In particular, the DC superposition characteristics of each Example in which D50 was 8.0 μm or more and 45.0 μm or less were further improved.
[0189] (Experimental Example 4)
[0190] Sample Nos. 1 and 6 were tested under substantially the same conditions except that the volume-based median diameter (D50) of powder B was changed. The results are shown in Table 4.
[0191]
Table 4
[0192]
[0193] According to Table 4, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in each embodiment in which the DC superposition characteristics are sufficiently improved and the core loss is improved even if the volume-based median particle size (D50) of powder B is changed by agglomerating powder B to satisfy 1.0μm<M<(0.5×D50).
[0194] (Experimental Example 5)
[0195] In Experimental Example 5, the same conditions as those of Sample Nos. 1 and 6 were used except that the coating was formed by insulating coating on Powder A. Specifically, Powder A was subjected to coating treatment using a mechanical fusion device (manufactured by Hosokawa Micron Corporation: AMS-Lab), and a coating of P-Zn-Al-O oxide glass was formed on the surface. The thickness of the coating was 15 nm. The results are shown in Table 5.
[0196]
Table 5
[0197]
[0198] According to Table 5, compared with the comparison example (sample number 36) which has essentially the same conditions except that M is too small because the powder B is not agglomerated, in the embodiment (sample number 37) in which the DC superposition characteristics are sufficiently improved and the core loss is improved even when the coating is formed by insulating coating, the powder B is agglomerated to satisfy 1.0μm<M<(0.5×D50).
[0199] (Experimental Example 6)
[0200] The test was carried out under the same conditions as those of Sample Nos. 1 and 6 except that the composition and microstructure of the powder A were changed. The results are shown in Table 6.
[0201] In sample numbers 38 and 39, the composition of powder A was set to 66.8Fe-16.7Co-11.0B-4.5P-1.0Si in terms of atomic ratio. In sample numbers 40 and 41, the composition of powder A was set to 72.7Fe-10.8B-11.6Si-2.7C-2.2Cr in terms of atomic ratio. In sample numbers 42 and 43, the composition of powder A was set to 81.6Fe-13.4B-3.4Si-1.6C in terms of atomic ratio. It was confirmed by XRD that all powders A of sample numbers 38 to 43 had a structure composed of amorphous materials.
[0202] In sample numbers 44 and 45, the composition of powder A is set to 73.5Fe-13.5Si-9.0B-3.0Nb-1.0Cu in terms of atomic ratio. In sample numbers 46 and 47, the composition of powder A is set to 82.0Fe-11.0B-5.0P-1.0Si-1.0Cu in terms of atomic ratio. In sample numbers 48 and 49, the composition of powder A is set to 78.0Fe-9.0B-3.0P-3.0Si-6.0Nb-1.0Cr in terms of atomic ratio. In addition, for powders A of sample numbers 44 to 49, heat treatment is performed after being produced by gas atomization to precipitate nanocrystals with a crystal particle size of less than 30nm, thereby reducing the amorphization rate X to 10%. Regarding the heat treatment, specifically, it is performed at 400 to 650°C for 10 to 60 minutes. It was confirmed by XRD that all of the powders A of sample numbers 44 to 49 had a structure composed of nanocrystals.
[0203] In sample numbers 50 and 51, the composition of powder A was set to a composition containing substantially only Fe. In sample numbers 52 and 53, the composition of powder A was set to 50.0Fe-50.0Co in terms of atomic ratio. In sample numbers 54 and 55, the composition of powder A was set to 83.6Fe-4.4Co-12.0Si in terms of atomic ratio. In sample numbers 56 and 57, the composition of powder A was set to 89.4Fe-8.6Si-2.0Cr. In sample numbers 58 and 59, the composition of powder A was set to 80.5Fe-9.0Co-8.5Si-2.0Cr. In sample numbers 60 and 61, the composition of powder A was set to 73.7Fe-16.4Si-9.9Al. It was confirmed by XRD that powders A of sample numbers 50 to 61 all had a structure composed of crystals.
[0204]
Table 6
[0205]
[0206] According to Table 6, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even if the composition and microstructure of powder A are changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0207] (Experimental Example 7)
[0208] Sample Nos. 1 and 6 were tested under the same conditions except that the composition of powder A was changed. The composition of powder A was mainly changed in the total content ratio of Fe and Co. The results are shown in Table 7. For Experimental Examples 7 to 12, the description of comparative examples with substantially the same conditions as the samples was omitted except that M was too small because powder B was not agglomerated.
[0209]
Table 7
[0210]
[0211] According to Table 7, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0212] In particular, the Isat improvement rate of sample numbers 102 to 117, in which the total content of Fe and Co is 70.00 at% or more and 96.00 at% or less, is better than that of sample numbers 101 and 118, in which the total content of Fe and Co is outside the above range. It is believed that the Isat improvement rate of sample number 101 is low because the magnetic properties are lower than those of other samples due to the small content of magnetic elements. It is also believed that the Isat improvement rate of sample number 118 is low because the amorphous nature of powder A is lower than that of other samples, so the magnetic properties are lower than those of other samples.
[0213] (Experimental Example 8)
[0214] The comparative example and sample number 106 were run under substantially the same conditions as sample number 106 except that powder B was not agglomerated and M was too small, but the contents of Fe, Co, and Ni in powder A were changed. The results are shown in Table 8.
[0215]
Table 8
[0216]
[0217] According to Table 8, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0218] In particular, the Isat improvement rates of sample numbers 106, 121 to 125, 127 to 131, and 133 to 136, in which the Fe content is greater than the total content of Co and Ni, are better than those of sample numbers 126, 132, and 137, in which the Fe content is less than the total content of Co and Ni. It is also considered that the Isat improvement rates of sample numbers 126, 132, and 137 are low because the magnetic properties are lower than those of other samples.
[0219] (Experimental Example 9)
[0220] Sample Nos. 40 and 41 were tested by mainly changing the C content and the Cr content of the powder A. Table 9 shows the results.
[0221]
Table 9
[0222]
[0223] According to Table 9, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0224] In particular, compared with sample number 141 in which the content of X2 exceeds 3.00 at% and sample number 151 in which the content of C exceeds 5.00 at%, the Isat improvement rates of sample numbers 41, 142 to 150 in which the content of C is 0 at% to 5.00 at% and the content of X2 (Cr) is 0 at% to 3.00 at% are better. It is believed that the Isat improvement rate of sample number 141 is low because the more X2, the easier it is to reduce the magnetic properties, especially the saturation magnetic flux density. It is believed that the Isat improvement rate of sample number 151 is low because the amorphous property is reduced by containing a lot of C, and the magnetic properties are reduced.
[0225] (Experimental Example 10)
[0226] Sample Nos. 42 and 43 were tested by changing the content of B and Fe in powder A. Sample Nos. 44 and 45 were tested by changing the content of B and Si in powder A. Sample Nos. 46 and 47 were tested by changing the content of B and Si in powder A. Sample Nos. 48 and 49 were tested by changing the content of B, P, and Nb in powder A. The results are shown in Table 10.
[0227]
Table 10
[0228]
[0229] According to Table 10, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0230] In particular, compared with sample number 169 having a B content exceeding 20.00 at%, sample number 171 having a Si content exceeding 15.00 at%, sample number 186 having a B content below 2.00 at%, and sample number 191 having a X3 content exceeding 9.00 at%, sample numbers 43, 45, 47, 49, 161 to 168, 172 to 175, 181 to 185, and 192 to 196 having a B content of 2.00 at% to 20.00 at%, a Si content of 0 at% to 15.00 at%, and a X3 (Nb) content of 0 at% to 9.00 at%, the Isat improvement rates are better. It is considered that the Isat improvement rates of sample numbers 169 and 186 are low because the magnetic properties are reduced due to the reduction of amorphous properties regardless of whether the B content is too high or too low. It is also believed that the reason why the Isat improvement rate of sample number 171 is low is that the saturation magnetic flux density is reduced due to the large amount of Si contained, and the magnetic properties are reduced. It is also believed that the reason why the Isat improvement rate of sample number 191 is low is that the Curie point is reduced due to the large amount of X3 contained, and the saturation magnetic flux density at room temperature is reduced, and the magnetic properties are reduced.
[0231] (Experimental Example 11)
[0232] The comparative examples and samples were substantially the same as the samples except that M was too small because the powder B was not agglomerated, and the type and / or content of X2 in the powder A were changed. In addition, the sample number 200 did not contain X2, and in the sample numbers 201 to 262, part of Fe and Co in the sample number 200 was replaced with X2. The results are shown in Tables 11A to 11C.
[0233]
Table 11A
[0234]
[0235]
Table 11B
[0236]
[0237]
Table 11C
[0238]
[0239] According to Tables 11A to 11C, compared to the comparison examples with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which the DC superposition characteristics are sufficiently improved and the core loss is improved even if the composition of powder A is changed by agglomerating powder B to satisfy 1.0μm<M<(0.5×D50).
[0240] (Experimental Example 12)
[0241] The comparative example and sample number 106 were substantially the same as sample number 106 except that M was too small because powder B was not agglomerated. The same conditions were used except that X2 (Cr) of powder A was replaced with X3 (Nb). In addition, the type and content of X3 were changed, and the content of B, the content of P, and the content of Si were changed in accordance with the change of the content of X3. The results are shown in Table 12.
[0242]
Table 12
[0243]
[0244] According to Table 12, compared with the comparison example which has essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0245] In particular, the Isat improvement rates of Sample Nos. 271 to 274, 276 to 279, 281 to 284, 286 to 289, 291 to 294, and 296 to 299, which have X3 contents of 0 to 9.00 at%, are better than those of Sample Nos. 275, 280, 285, 290, 295, and 300, which have X3 contents exceeding 9.00 at%. It is believed that the low Isat improvement rates of Sample Nos. 275, 280, 285, 290, 295, and 300 are because, due to the large amount of X3 contained, the Curie point is lowered, the saturation magnetic flux density at room temperature is lowered, and the magnetic properties are lowered.
[0246] (Experimental Example 13)
[0247] The test was carried out under the same conditions as those of Sample Nos. 1 and 6 except that the composition of the powder B was changed. The results are shown in Table 13. In each sample, the powder B was appropriately prepared by a known method.
[0248] In sample numbers 62 and 63, the composition of powder B was set to a composition containing essentially only Co. In sample numbers 64 and 65, the composition of powder B was set to 50.0Fe-50.0Co in terms of atomic ratio. In sample numbers 66 and 67, the composition of powder B was set to 90.0Fe-10.0Si in terms of atomic ratio. In sample numbers 68 and 69, the composition of powder B was set to 20.0Fe-80.0Ni in terms of atomic ratio. It was confirmed by XRD that all powders B of sample numbers 62 to 69 had a structure composed of crystals.
[0249]
Table 13
[0250]
[0251] According to Table 13, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which the DC superposition characteristics are sufficiently improved and the core loss is improved even if the composition and microstructure of powder B are changed and powder B is agglomerated to satisfy 1.0μm<M<(0.5×D50), the DC superposition characteristics are improved.
[0252] (Experimental Example 14)
[0253] Sample Nos. 56 and 57 were run under substantially the same conditions except that the volume-based median diameter (D50) of powder A was changed. The results are shown in Table 14.
[0254]
Table 14
[0255]
[0256] According to Table 14, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in each embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even if the volume-based median particle size (D50) of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0257] In particular, the DC superposition characteristics of each Example in which D50 was 8.0 μm or more and 45.0 μm or less were further improved.
[0258] Experimental Example 3 and Experimental Example 14 are experiments conducted for the same purpose except that the composition and microstructure of the powder A are different.
[0259] (Experimental Example 15)
[0260] The same conditions as those of Sample Nos. 1, 6, and 12 to 17 of Experimental Examples 1 and 2 were used, except that a portion of Powder B having a median particle size of 0.8 μm on a volume basis was replaced with Powder C, which was a carbonyl iron powder identical to Powder B except that the median particle size on a volume basis was 3 μm. In addition, Powder C did not aggregate, unlike Powder B. The results are shown in Table 15.
[0261]
Table 15
[0262]
[0263] According to Table 15, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, even in the embodiment where powder C is used in addition to powder A and powder B, the DC superposition characteristics are sufficiently improved and the core loss is improved by agglomerating powder B to satisfy 1.0μm<M<(0.5×D50).
[0264] (Experimental Example 16)
[0265] The experiment was carried out under the same conditions as those of Sample Nos. 70 and 71 of Experimental Example 15, except that the composition and microstructure of the powder C were changed. The results are shown in Table 16.
[0266] The composition and microstructure of the powder C in sample numbers 78 and 79 were made the same as the composition and microstructure of the powder B in sample numbers 62 and 63. The composition and microstructure of the powder C in sample numbers 80 and 81 were made the same as the composition and microstructure of the powder B in sample numbers 64 and 65. The composition and microstructure of the powder C in sample numbers 82 and 83 were made the same as the composition and microstructure of the powder B in sample numbers 66 and 67. The composition and microstructure of the powder C in sample numbers 84 and 85 were made the same as the composition and microstructure of the powder B in sample numbers 68 and 69. In each of sample numbers 78 to 85, the powder C was appropriately prepared by a known method.
[0267] The composition and microstructure of the powder C in sample numbers 86 and 87 were made the same as the composition and microstructure of the powder A in sample numbers 38 and 39. The composition and microstructure of the powder C in sample numbers 88 and 89 were made the same as the composition and microstructure of the powder A in sample numbers 40 and 41. The composition and microstructure of the powder C in sample numbers 90 and 91 were made the same as the composition and microstructure of the powder A in sample numbers 44 and 45. The composition and microstructure of the powder C in sample numbers 92 and 93 were made the same as the composition and microstructure of the powder A in sample numbers 46 and 47. The composition and microstructure of the powder C in sample numbers 94 and 95 were made the same as the composition and microstructure of the powder A in sample numbers 48 and 49. In each of sample numbers 86 to 95, the powder C was appropriately produced by the gas atomization method in the same manner as the powder A.
[0268]
Table 16
[0269]
[0270] According to Table 16, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 1.0μm<M<(0.5×D50) is satisfied by agglomerating powder B even if the composition and microstructure of powder C are further changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0271] (Experimental Example 17)
[0272] In Experimental Example 17, a powder A, which was mostly large particles in many examples, was produced by water atomization. The composition of the powder A was set to be a composition of the Fe-Co-BP-Si-Cr system. Specifically, in terms of atomic ratio, it was set to be a composition of 57.4Fe-24.6Co-11.0B-3.0P-3.0Si-1.0Cr.
[0273] Regarding the conditions of the water atomization method, the pressure of high-pressure water is set to 50.0 MPa to 200 MPa, and the ejection rate of the molten metal is set to 0.5 kg / min to 4.0 kg / min.
[0274] The classification method of the powder prepared by the water atomization method is described. First, the obtained powder is sieved using a sieve with a mesh size of 250 μm to remove coarse particles. Next, air flow classification is performed so that the median particle size (D50) of the powder A based on volume becomes the target value. The air flow classification is performed by using an air flow classifier (FACULTY manufactured by Hosokawa Micron Corporation) as a classification device and setting the classification rotor speed to 4000 rpm or more and 20000 rpm or less.
[0275] The atomization conditions and the classification conditions in the air flow classification were appropriately controlled so that D50 of the obtained powder A became the values shown in Table 17.
[0276] For each sample, ICP analysis confirmed that the composition of the master alloy was substantially the same as that of the powder A. The median particle size (D50) of the obtained powder A on a volume basis was confirmed to be the value shown in Table 17. The median particle size of the powder A on a volume basis was measured by laser diffraction using a dry particle size distribution measuring apparatus.
[0277] Carbonyl iron powder is used as powder B, which ultimately becomes mostly particles other than large particles in many embodiments. That is, the composition of the soft magnetic particles contained in powder B is made to be a composition containing essentially only Fe. In addition, by using an air flow classifier to appropriately remove coarse powder and / or fine powder, the median particle size (D50) of powder B on a volume basis is made to be 0.8 μm. By ICP analysis, it is confirmed that the composition of powder B is the target composition. Using a dry particle size distribution measuring device, it is confirmed by laser diffraction that the median particle size (D50) of the obtained powder B on a volume basis is 0.8 μm.
[0278] Each powder was subjected to X-ray diffraction measurement (XRD) to measure the amorphization rate X. When the amorphization rate X is 85% or more, it has a structure composed of amorphous. When the amorphization rate X is less than 85% and the average crystal particle size is less than 100nm, it has a structure composed of nanocrystals. When the amorphization rate X is less than 85% and the average crystal particle size is greater than 100nm, it has a structure composed of crystals. In Experimental Example 17, it was confirmed that all powders A had a structure composed of amorphous, and all powders B had a structure composed of crystals.
[0279] Next, powder B is agglomerated. First, powder B and epoxy resin are mixed. The amount of epoxy resin added to powder B is set to 0.2 parts by mass relative to 100 parts by mass of powder B. Next, 1 g of powder B mixed with epoxy resin is filled into a cylindrical mold with a diameter of 8 mm Φ. Next, it is agglomerated by compressing at the pressure value shown in Table 17. In the case of producing more than 1 g of agglomerated powder B, the above steps are repeated multiple times. In addition, in sample numbers 301, 303, 305, 307, 309, 311, 313, 315, and 317, powder B is not compressed and is not agglomerated.
[0280] Next, powder A, condensed powder B, and epoxy resin are kneaded to obtain a resin mixture. In addition, in sample numbers 301, 303, 305, 307, 309, 311, 313, 315, and 317, powder A, powder B, and epoxy resin are kneaded to obtain a resin mixture. The mixing ratio of powder A and powder B is set to 80:20 on a mass basis. The total amount of powder A and powder B is set to 100 parts by mass, and the content of epoxy resin is set to 2.0 parts by mass to 3.0 parts by mass. The amount of epoxy resin added is controlled so that the relative magnetic permeability μ of the final magnetic core becomes 30.
[0281] Next, the resin mixture is filled into a ring-shaped mold and press-molded to obtain a ring-shaped molded body. The molding pressure is appropriately controlled within a range of 98 MPa to 981 MPa so that the relative magnetic permeability μ of the finally obtained magnetic core becomes 30.
[0282] Then, the epoxy resin contained in the obtained molded body was thermally cured to obtain a magnetic core. The heat treatment conditions were set at 180° C. for 60 minutes. The dimensions of the magnetic core were set to an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a thickness of 2.5 mm.
[0283] The cross section of the magnetic core of each sample cut parallel to the molding direction (height direction) was observed using SEM (SU-5000 manufactured by HITACHI HIGH-TECH CORPORATION), and D50 was calculated by the above method.
[0284] Furthermore, M was calculated by the above method and compared with 0.35 μm and D50 / 2. The results are shown in Table 17.
[0285] The relative magnetic permeability μ, DC superposition characteristic Isat, and core loss of the toroidal core of each sample were measured in the same manner as in Experimental Example 1.
[0286] Table 17 shows the improvement rate of Isat relative to the Isat of the sample with the same conditions except that the powder B was not agglomerated. When D50 was less than 4.0 μm, the improvement rate of Isat was 0.2% or more, which was considered to be good DC superposition characteristics, 0.5% or more, which was considered to be more good DC superposition characteristics, and 1.0% or more, which was considered to be particularly good DC superposition characteristics. The results are shown in Table 17.
[0287] The improvement rate of the core loss of the sample under the same conditions except that the powder B was not agglomerated was used as a reference, and the improvement rate of the core loss relative to the core loss of the sample was calculated. The results are shown in Table 17. When D50 is less than 4.0 μm, the improvement rate of the core loss is good when it is 2.0% or more, and it is better when it is 5.0% or more, and it is better when it is 10.0% or more, and it is particularly good when it is 15.0% or more. The results are shown in Table 17.
[0288]
Table 17
[0289]
[0290] According to Table 17, in each embodiment in which 0.35 μm<M<(0.5×D50) is satisfied by agglomerating powder B, the DC superposition characteristics are improved and the core loss is improved, compared with the comparative example in which M is too small because powder B is not agglomerated. However, in the comparative example (sample number 302) in which powder B is agglomerated but D50 is too small, the core loss is not improved compared with sample number 301 which has the same conditions except that powder B is not agglomerated.
[0291] According to Table 17, compared with the comparison example which has essentially the same conditions except that M is too small because powder B is not agglomerated, in each embodiment in which the volume-based median particle size (D50) of powder A is varied within a prescribed range and powder B is agglomerated to satisfy 0.35μm<M<(0.5×D50), the DC superposition characteristics are substantially improved and the core loss is improved.
[0292] In particular, the improvement rate of the core loss of each example with D50 of 1.0 μm to 3.5 μm is more favorable. In addition to the improvement rate of the core loss, each example with D50 of 2.0 μm to 3.5 μm also has better DC superposition characteristics.
[0293] (Experimental Example 18)
[0294] Sample Nos. 313 and 314 were tested under the same conditions except that the composition of powder A was changed. The composition of powder A was mainly changed by changing the total content ratio of Fe and Co. The results are shown in Table 18. For Experimental Examples 18 to 23, the description of comparative examples with substantially the same conditions as the samples was omitted except that M was too small because powder B was not agglomerated. In addition, Isat and core loss were omitted in Tables 18 to 23.
[0295]
Table 18
[0296]
[0297] According to Table 18, compared with the comparison example which has essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which the DC superposition characteristics are sufficiently improved and the core loss is improved even if the composition of powder A is changed but powder B is agglomerated to satisfy 0.35μm<M<(0.5×D50).
[0298] In particular, sample numbers 314 and 322 to 337 having a total content of Fe and Co of 70.00 at % to 96.00 at % showed better improvement in core loss than sample numbers 321 and 338 having a total content of Fe and Co outside the above range.
[0299] Sample No. 321 has a small content of magnetic elements, so the soft magnetic properties of powder A are lower than those of other samples. Sample No. 338 has a lower amorphous nature than other samples, so the soft magnetic properties of powder A are lower than those of other samples.
[0300] It is considered that the improvement rate of the core loss of sample numbers 321 and 338 is low because the soft magnetic properties of powder A are low and the influence on the core loss of M is also low.
[0301] (Experimental Example 19)
[0302] The comparative example and sample number 326 were subjected to substantially the same conditions as sample number 326 except that powder B was not agglomerated and M was too small, but the contents of Fe, Co, and Ni in powder A were changed. The results are shown in Table 19.
[0303]
Table 19
[0304]
[0305] According to Table 19, compared with the comparison example which has essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which the DC superposition characteristics are substantially improved and the core loss is improved even if the composition of powder A is changed but powder B is agglomerated to satisfy 0.35μm<M<(0.5×D50).
[0306] In particular, the improvement rate of the core loss of sample numbers 326, 341 to 345, 347 to 351, and 353 to 356, in which the content of Fe is greater than the total content of Co and Ni, is better than that of sample numbers 346, 352, and 357, in which the content of Fe is less than the total content of Co and Ni. It is also believed that the improvement rate of the core loss of sample numbers 346, 352, and 357 is low because the soft magnetic properties of powder A are lower than those of other samples.
[0307] (Experimental Example 20)
[0308] The same procedure as sample numbers 40 and 41 was performed except that the median particle size of powder A was changed. Sample number 368 was a sample that was performed in the same manner as sample number 41 except that the median particle size of powder A was changed.
[0309] Furthermore, the comparative example and sample number 368 were conducted under substantially the same conditions as sample number 368 except that M was too small because powder B was not agglomerated, and mainly the C content and Cr content of powder A were changed. The results are shown in Table 20.
[0310]
Table 20
[0311]
[0312] According to Table 20, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 0.35μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0313] In particular, compared with sample number 361 in which the content of X2 exceeds 3.00 at% and sample number 372 in which the content of C exceeds 5.00 at%, the improvement rate of the core loss of sample numbers 362 to 371 in which the content of C is 0 at% to 5.00 at% and the content of X2 (Cr) is 0 at% to 3.00 at% is better. It is believed that the improvement rate of the core loss of sample number 361 is low because the more X2, the easier it is for the soft magnetic properties of powder A to decrease. It is believed that the improvement rate of the core loss of sample number 372 is low because the amorphous nature of powder A is reduced by containing a lot of C, and the soft magnetic properties of powder A are reduced.
[0314] (Experimental Example 21)
[0315] The same method as sample numbers 42 and 43 was used except that the median particle size of powder A was changed. The sample that was used in the same way as sample number 43 except that the median particle size of powder A was changed was set as sample number 384. In addition, the comparative example and sample number 384, which were substantially the same as sample number 384 except that M was too small because powder B was not agglomerated, were mainly used to change the content of B and the content of Fe in powder A. The results are shown in Table 21.
[0316] The same method as sample numbers 44 and 45 was used except that the median particle size of powder A was changed. The sample that was used in the same way as sample number 45 except that the median particle size of powder A was changed was set as sample number 394. Furthermore, the comparative example and sample number 394, which were substantially the same as sample number 394 except that M was too small because powder B was not agglomerated, were mainly used to change the B content and Si content of powder A. The results are shown in Table 21.
[0317] The same method as sample numbers 46 and 47 was used except that the median particle size of powder A was changed. The sample that was used in the same way as sample number 47 except that the median particle size of powder A was changed was set as sample number 397. Furthermore, the comparative example and sample number 397, which were substantially the same as sample number 397 except that M was too small because powder B was not agglomerated, were mainly used to change the B content and Si content of powder A. The results are shown in Table 21.
[0318] The same method as sample numbers 48 and 49 was used except that the median particle size of powder A was changed. The sample that was used in the same way as sample number 49 except that the median particle size of powder A was changed was set as sample number 407. Furthermore, the comparative example and sample number 407 that were substantially the same as sample number 407 except that M was too small because powder B was not agglomerated were used, and the B content, P content, and Nb content of powder A were mainly changed and used. The results are shown in Table 21.
[0319]
Table 21
[0320]
[0321] According to Table 21, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 0.35μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0322] In particular, the improvement rate of the core loss of samples No. 381 to 389, 392 to 402, and 405 to 410, in which the content of B is 2.00 at% to 20.00 at%, the content of Si is 0 at% to 15.00 at% and the content of X3 (Nb) is 0 at% to 9.00 at% is better than that of sample No. 390 in which the content of B exceeds 20.00 at%, sample No. 391 in which the content of Si exceeds 15.00 at%, sample No. 403 in which the content of B is less than 2.00 at%, and sample No. 404 in which the content of X3 exceeds 9.00 at%. It is also considered that the improvement rate of the core loss of sample No. 390 and 403 is low because the soft magnetic properties of powder A are reduced due to the reduction of the amorphous nature of powder A regardless of whether the content of B is too much or too little. The reason why the improvement rate of the core loss of sample No. 391 is low is that the saturation magnetic flux density of powder A is reduced and the soft magnetic properties are reduced by containing a lot of Si. The reason why the improvement rate of the core loss of sample No. 404 is low is that the Curie point is reduced and the saturation magnetic flux density of powder A at room temperature is reduced and the soft magnetic properties are reduced by containing a lot of X3.
[0323] (Experimental Example 22)
[0324] The comparative examples and samples were substantially the same as the samples except that M was too small because the powder B was not agglomerated, and the test was performed mainly by changing the type and / or content of X2 in the powder A. In addition, the sample number 420 did not contain X2, and in the sample numbers 421 to 482, part of Fe and Co in the sample number 420 was replaced with X2. The results are shown in Tables 22A to 22C.
[0325] Table 22A
[0326]
[0327]
Table 22B
[0328]
[0329]
Table 22C
[0330]
[0331] According to Tables 22A to 22C, compared to the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which the DC superposition characteristics are sufficiently improved and the core loss is improved even if the composition of powder A is changed by agglomerating powder B to satisfy 0.35μm<M<(0.5×D50).
[0332] (Experimental Example 23)
[0333] The comparative example and sample number 326 were substantially the same as sample number 326 except that M was too small because powder B was not agglomerated. The same conditions were used except that X2 (Cr) of powder A was replaced with X3 (Nb). In addition, the type and content of X3 were changed, and the content of B, the content of P, and the content of Si were changed in accordance with the change of the content of X3. The results are shown in Table 23.
[0334]
Table 23
[0335]
[0336] According to Table 23, compared with the comparison example with essentially the same conditions except that M is too small because powder B is not agglomerated, in the embodiment in which 0.35μm<M<(0.5×D50) is satisfied by agglomerating powder B even when the composition of powder A is changed, the DC superposition characteristics are sufficiently improved and the core loss is improved.
[0337] In particular, the improvement rate of the core loss of sample numbers 491 to 494, 496 to 499, 501 to 504, 506 to 509, 511 to 514, and 516 to 519, in which the content of X3 is 0 at% to 9.00 at%, is better than that of sample numbers 495, 500, 505, 510, 515, and 520, in which the content of X3 exceeds 9.00 at%. It is believed that the improvement rate of the core loss of sample numbers 495, 500, 505, 510, 515, and 520 is low because the Curie point of powder A is lowered by containing a lot of X3, the saturation magnetic flux density of powder A at room temperature is lowered, and the soft magnetic properties are lowered.
[0338] The soft magnetic particles contained in the magnetic cores of the samples obtained in Experimental Examples 1 to 23 were examined by electron diffraction patterns using TEM to confirm their microstructures. It was confirmed that the microstructures of the soft magnetic particles derived from powder A, the soft magnetic particles derived from powder B, and the soft magnetic particles derived from powder C did not substantially change before and after molding.
Claims
1. A magnetic core, wherein: The magnetic core contains soft magnetic particles. In the volume-based particle size distribution of the soft magnetic particles, the soft magnetic particles having a particle diameter of 0.5×D50 or more are defined as large particles, When the average value of the distance from a certain large particle to the three large particles closest to the large particle is set as AL, and the median value of AL calculated for all large particles is set as M, Satisfies 1.0μm<M<0.5×D50.
2. The magnetic core according to claim 1, wherein: D50 is 4.0 μm or more and 60.0 μm or less.
3. The magnetic core according to claim 1 or 2, wherein: At least a portion of the soft magnetic particles has a composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f express, X1 is one or more selected from Co and Ni, X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements, X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W, Satisfies 0≤p≤0.5, 2.00≤a≤20.00、 0.00≤b≤14.00、 0.00≤c≤15.00、 0.00≤d≤5.00、 0.00≤e≤3.00、 0.00≤f≤9.00, and 70.00≤100-(a+b+c+d+e+f)≤96.
00.
4. The magnetic core according to claim 1 or 2, wherein: At least a part of the soft magnetic particles contains only Fe, or contains Fe and Co and / or Ni.
5. A magnetic core, wherein: The magnetic core contains soft magnetic particles. In the volume-based particle size distribution of the soft magnetic particles, the soft magnetic particles having a particle diameter of 0.5×D50 or more are defined as large particles, When the average value of the distance from a certain large particle to the three large particles closest to the large particle is set as AL, and the median value of AL calculated for all large particles is set as M, Satisfies 0.35μm<M<0.5×D50, and D50 is 0.80 μm or more and less than 4.0 μm.
6. The magnetic core according to claim 5, wherein: At least a portion of the soft magnetic particles has a composition formula (Fe 1-p X1 p ) 100-(a+b+c+d+e+f) B a P b Si c C d X2 e X3 f express, X1 is one or more selected from Co and Ni, X2 is one or more selected from Ti, Cr, Mn, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, Au, Cu, rare earth elements and platinum group elements, X3 is one or more selected from Zr, Nb, Mo, Hf, Ta, and W, Satisfies 0≤p≤0.5, 2.00≤a≤20.00、 0.00≤b≤14.00、 0.00≤c≤15.00、 0.00≤d≤5.00、 0.00≤e≤3.00、 0.00≤f≤9.00, and 70.00≤100-(a+b+c+d+e+f)≤96.
00.
7. The magnetic core according to claim 5 or 6, wherein: At least a part of the soft magnetic particles contains only Fe, or contains Fe and Co and / or Ni.
8. A magnetic component, wherein: A magnetic core comprising the magnetic core according to any one of claims 1 to 7.
9. An electronic device, wherein: A magnetic core comprising the magnetic core according to any one of claims 1 to 7.
Citation Information
Patent Citations
Odakusuino jokasochi
JP1976010660A
Coil encapsulating magnetic component and method of manufacturing the same
JP2003309024A
Composite magnetic material, core using the same, and magnetic element
JP2004197218A
Complex magnetic material and method for manufacturing inductor using the same
JP2004363466A